2019
DOI: 10.1051/0004-6361/201629162
|View full text |Cite
|
Sign up to set email alerts
|

Highly luminous supernovae associated with gamma-ray bursts

Abstract: Context. GRB 111209A, one of the longest gamma-ray bursts (GRBs) ever observed, is linked to SN 2011kl, which is the most luminous GRB supernova (SN) detected so far. Several lines of evidence indicate that this GRB-SN is powered by a magnetar central engine. Aims. We place SN 2011kl into the context of large samples of SNe, addressing in more detail the question of whether this GRB-SN could be radioactively powered, and whether it represents an extreme version of a GRB-SN or an underluminous superluminous SN … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
43
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 255 publications
3
43
1
Order By: Relevance
“…iPTF16asu was discovered by the intermediate Palomar Transient Factory (iPTF; Law et al 2009;Cao et al 2016;Masci et al 2017) on 2016 May 11.26 UT. It represents one of the most luminous type Ic SNe, with an absolute magnitude of −20.4 mag in g band, similar to the luminous transients (Drout et al 2011(Drout et al , 2014Greiner et al 2015;Wang et al 2015b;Arcavi et al 2016;Kann et al 2019) discovered recently. Thanks to the wide field and high cadence of iPTF, the rapid rise of the light curve of iPTF16asu (4 days to peak luminosity since the discovery) was captured.…”
supporting
confidence: 71%
“…iPTF16asu was discovered by the intermediate Palomar Transient Factory (iPTF; Law et al 2009;Cao et al 2016;Masci et al 2017) on 2016 May 11.26 UT. It represents one of the most luminous type Ic SNe, with an absolute magnitude of −20.4 mag in g band, similar to the luminous transients (Drout et al 2011(Drout et al , 2014Greiner et al 2015;Wang et al 2015b;Arcavi et al 2016;Kann et al 2019) discovered recently. Thanks to the wide field and high cadence of iPTF, the rapid rise of the light curve of iPTF16asu (4 days to peak luminosity since the discovery) was captured.…”
supporting
confidence: 71%
“…Note that the peak mag of iPTF15ul includes a large host-galaxy extinction correction, whereas the other sources have zero host extinction correction. Also note that SN 2011kl was associated with an ultra-long duration GRB 111209A (Kann et al 2018), and the light-curve properties shown here reflect the afterglowsubtracted light curve (Kann et al 2019). On 2019 January 4 (+115 days), we obtained a spectrum of the host galaxy of ZTF18abvkwla using the Low Resolution Imaging Spectrometer (Oke et al 1995;McCarthy et al 1998) on the Keck I 10 m telescope, with the 400/3400 grism in the blue camera and the 400/8500 grating in the red camera.…”
mentioning
confidence: 79%
“…This results in the typically larger explosion energies and luminosities and temperatures of GRB-SNe cf. standard CCSNe (Lyman et al 2016;Modjaz et al 2016;Kann et al 2019;Taddia et al 2019). The geometric alignment of these bi-polar jets and the Earth may be the single greatest factor in determining whether a GRB is detected associated with a collapsar SN.…”
Section: Introductionmentioning
confidence: 99%